Current Status of Urinary Schistosomiasis Among Communities in Kurmuk District, Western Ethiopia: Prevalence and Intensity of Infection - Tigist Mohammed; Wei Hu; Mulugeta Aemero; Yirgalem Gebrehiwot; Berhanu Erko (SAGE Publishing, 2023)
Background: Schistosomiasis is a highly prevalent but neglected tropical disease, particularly in sub-Saharan Africa. In Ethiopia, urogenital schistosomiasis due to Schistosoma haematobium has been known to be endemic in several lowland areas. This study was designed to determine the current prevalence and intensity of the urogenital schistosomiasis among communities in Kurmuk District, western Ethiopia. Methods: Urine filtration technique and urine dipstick test were used to screen for S. haematobium eggs and hematuria, respectively. The data were analyzed with SPSS version 23. Logistic regression and odds ratio were used to measure associations and strength between prevalence, intensity, and independent variables. P -values <.05 at 95% CI were considered statistically significant. Results: The overall prevalence of S. haematobium infection as determined by urine filtration was 34.2% (138/403). In bivariate analysis, the most infected (45.4%) age groups were 5 to 12 years (odds ratio [OR] = 4.16, 95% CI: 1.36-12.67), followed by 13 to 20 years (OR = 3.23, 95% CI: 1.01-10.35) with higher significant mean egg count (MEC). The mean egg intensity ranged from 2.39 in Ogendu (CI: 1.05-3.72) to 14.1 in Dulshatalo (CI: 4.98-23.12) villages. The main predictor of infection was swimming habits (adjusted odds ratio [AOR] = 2.43 [CI: 1.19-4.94]). The prevalence of hematuria was 39.2% (158/403), the odds being 2.64 times higher among participants who resided in Dulshatalo than those who resided in Kurmuk (AOR 2.64 [95% CI: 1.43-4.87], P  = .004). Conclusion: To reduce the infection and interrupt transmission, the PC in place in the area using PZQ should be strengthened and continued, alongside with provision of sanitary facilities, safe alternative water supplies and health education. The Federal Ministry of Health of Ethiopia should also collaborate with the health authorities of the Sudan government for the control of trans-boundary transmission of the disease as the transmission foci are shared between the 2 countries.